2023
DOI: 10.3390/horticulturae9030365
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Irrigation Intervals and NPK/Yeast on the Vegetative Growth Characteristics and Essential Oil Content of Lemongrass

Abstract: The growth and quality of medicinal plants are greatly affected by environmental stress, with over half of the world’s agricultural land facing water shortages. This research was conducted over two seasons in 2018 and 2019 and aimed to investigate the influence of varying irrigation intervals and partial replacement of mineral fertilizers with biofertilizer (yeast) on the growth, yield, and essential oil content of lemongrass. The study also looked at the effect of the partial substitution of NPK fertilizer wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Shahi et al [ 46 ] revealed a PHT range of 35.7–166.7 cm and 16.0–90.0 NOT of C. flexuosus under different organic and inorganic soil amendments in India. Mahmoud et al [ 47 ] reported between 11.5 and 173.8 NOL of C. citratus due to various water intervals and NPK fertilizer application in Egypt. However, the inconsistency among these studies might depend on different harvesting times, soil conditioners and plant species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shahi et al [ 46 ] revealed a PHT range of 35.7–166.7 cm and 16.0–90.0 NOT of C. flexuosus under different organic and inorganic soil amendments in India. Mahmoud et al [ 47 ] reported between 11.5 and 173.8 NOL of C. citratus due to various water intervals and NPK fertilizer application in Egypt. However, the inconsistency among these studies might depend on different harvesting times, soil conditioners and plant species.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). A study by Mahmoud et al [ 47 ] associated a high number of leaves per hill of C. citratus with irrigation after every five days and 100 % NPK input.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous elements have been shown to alleviate the negative effects of drought stress. In addition to the macroelements N, P and K [5][6][7], B, Mn [8], Ca [9], Se [10], Si [11,12] and Zn [13] have also been reported to mitigate the negative effects of water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…If sufficient water is available to plants, the limiting factor is usually primarily N; although, depending on the properties of the soil, P and K are also important, so their adequate supply in the soil is crucial [28,29]. Most studies have evaluated the individual effects of N, P or K on the development and biomass production of plants during drought, while studies on the combined effects of these nutrients are scant [7,30]. To the best of our knowledge, the role of these three macroelements in grass biomass production, dry matter content and WUE has not yet been investigated in a factorial field experiment with four nutrient levels and three rainfall levels, thus enabling their effects to be compared and optimal supply levels to be determined.…”
Section: Introductionmentioning
confidence: 99%